Examining the efficacy of cooling pad technology to address increasing building cooling demand in Latvia - Prozuments, Aleksejs; Borodinecs, Anatolijs; Lebedeva, Kristina; Palcikovskis, Arturs (Frontiers in Built Environment, 2023)
Over the past decades there has been a strong evidence of a temperature rise across the world that has led to a growing concern of more extreme weather patterns and regular seasonal heat waves globally. As such, building occupants are at a continuously growing risk to overheating exposure inside the premises throughout the warm season of the year. This study investigates the utilization of cooling pad technology as a potential solution to enhance cooling efficiency. Compared to traditional cooling methods, the implementation of cooling pads leads to significant reductions in temperature and enhanced humidity control, while consuming relatively lower amounts of energy. The study contains a comprehensive analysis of the climatic conditions in Latvia, focusing on temperature and humidity variations throughout the year over the last decade in three cities–Riga, Daugavpils and Liepaja, that extensively represent the scope of climatic variations across Latvia, featuring coastal and continental climate patterns. This study aims to evaluate the effectiveness and suitability of cooling pad technology in Nordic climate, focusing on three Latvian cities. The novelty of the study lies in its analysis of cooling pad technology’s effectiveness in Nordic climatic conditions in addressing the increasing cooling demand. The paper examines the fundamental principles behind cooling pad technology, its impact on chiller performance, and its ability to optimize the cooling process. The utilization of cooling pad technology as an effective means to enhance cooling efficiency across the building stock to improve occupant comfort level and IEQ is highlighted. The results demonstrate 5.47% COP increase during average summer temperature conditions, and 17.78% COP increase in peak summer temperature conditions after implementation of cooling pads. This study contributes to the existing knowledge on cooling technologies, offering practical recommendations for the implementation of cooling pad systems use in Latvia and across the wider Nordic region, which is experiencing the gradual rise in summer temperature and humidity level.